Neoadjuvant radiation therapy and its impact on complications after pancreaticoduodenectomy for pancreatic cancer: analysis of the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP). Issue 4 (24th September 2013) - Cho, Sung W.; Tzeng, Ching‐Wei David; Johnston, W. Cory; Cassera, Maria A.; Newell, Philippa H.; Hammill, Chet W.; Wolf, Ronald F.; Aloia, Thomas A.; Hansen, Paul D.
Abstract Objectives This study investigated the impact of neoadjuvant radiation therapy (XRT) on postoperative outcomes following pancreaticoduodenectomy for pancreatic cancer. Methods The American College of Surgeons National Quality Improvement Program database was queried for the period 2005–2010 to assess complication rates following pancreaticoduodenectomy for pancreatic cancer. Two groups of patients were identified, comprising those who received neoadjuvant XRT and those who did not (control group). Results A total of 4416 patients were identified, including 200 in the XRT group and 4216 in the control group. There were differences in patient characteristics between the groups, including in age, hypertension and bilirubin level. Despite the fact that weight loss was more common, median operative time was longer (423 min versus 368 min; P < 0.001), and vascular reconstruction was more commonly required (20.5% versus 8.4%; P < 0.001) in the XRT group. In addition, the XRT group had a shorter median hospital stay than the control group (9 days versus 10 days; P = 0.005). Mortality (3.0% versus 2.7%; P = 0.818) and morbidity (40.5% versus 37.6%; P = 0.404) rates were not influenced by neoadjuvant XRT. Blood transfusion rates were increased in the XRT group (13.0% versus 7.4%; P = 0.003). Severe complications were influenced by age >70 years, American Society of Anesthesiologists (ASA) class >2, preoperative sepsis, dyspnoea, weight loss, impaired functional status, peripheral vascular disease and operative time of >8 h. Conclusions Neoadjuvant XRT is not associated with an increase in complications after pancreaticoduodenectomy.